2020
DOI: 10.3390/genes11090963
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Species Phylogeography of Arid-Zone Sminthopsinae (Marsupialia: Dasyuridae) Reveals Evidence of Refugia and Population Expansion in Response to Quaternary Change

Abstract: Historical population contraction and expansion events associated with Pleistocene climate change are important drivers of intraspecific population structure in Australian arid-zone species. We compared phylogeographic patterns among arid-adapted Dasyuridae (Sminthopsis and Planigale) with close phylogenetic relationships and similar ecological roles to investigate the drivers of phylogeographic structuring and the importance of historical refugia. We generated haplotype networks for two mitochondrial (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 74 publications
(126 reference statements)
1
9
0
Order By: Relevance
“…As shown in Fig. 2, there was no obvious variation among S. longicaudata samples, consistent with the study of Umbrello et al (2020), in which >30 long-tailed dunnarts showed no obvious phylogeographic structure within Western Australia. We note, however, that, to date, no DNA sequence data are available for long-tailed dunnart specimens from either South Australia or the Northern Territory.…”
Section: Genetic Variability Within a Lanigersupporting
confidence: 87%
“…As shown in Fig. 2, there was no obvious variation among S. longicaudata samples, consistent with the study of Umbrello et al (2020), in which >30 long-tailed dunnarts showed no obvious phylogeographic structure within Western Australia. We note, however, that, to date, no DNA sequence data are available for long-tailed dunnart specimens from either South Australia or the Northern Territory.…”
Section: Genetic Variability Within a Lanigersupporting
confidence: 87%
“…Thus, a third scenario of reconnection of previously separated refugial populations may also explain the substantial admixture and low differentiation between these genetic clusters. In fact, Umbrello et al, (2020) found evidence of population expansion in six small dasyurids across the Pilbara since the mid-late Pleistocene and the Last Glacial Maximum (LGM) and proposed that this followed the increased availability of arid habitat. Refugial separation prior to population expansion after the LGM has also been detected in sea spiders (Soler-Membrives, Linse, Miller, & Arango, 2017), mussels (Cunha, Lopes, Reis, & Castilho, 2011) and ants (Xun et al, 2016), with weak differentiation reflecting the loss of refugial genetic structure over time due to high dispersal capacities.…”
Section: Isolation-by-barrier: Snps Vs Microsatellitesmentioning
confidence: 99%
“…Situated in the Australian arid biome, the topographically complex Pilbara region is a biodiversity hotspot that supports rich faunal diversity including both endemic and widespread mammals (McKenzie, van Leeuwen, & Pinder, 2009). Despite this, functional connectivity in Pilbara mammals is poorly resolved and the few genetic studies in the region are based on microsatellite and mitochondrial markers and reveal low genetic structure (Hohnen et al, 2016;Levy et al, 2019;Umbrello, Didham, How, & Huey, 2020). Threats including resource extraction, grazing pressure, and inappropriate fire regimes all impact habitat connectivity in the Pilbara (Cramer et al, 2016), highlighting the need to understand functional connectivity in the region.…”
Section: Introductionmentioning
confidence: 99%
“…We examined the genealogy and population diversity of Trichosurus vulpecula across Australia with mtDNA D‐loop sequences (Neaves et al, 2016 ; Umbrello et al, 2020 ; Figure 1 ). Polymerase chain reaction (PCR) amplification targeted a 730 bp fragment of the mtDNA D‐loop with PCR primers Tcan_218f and Tvul_1023r designed for Trichosurus , using conditions described previously (Pattabiraman et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Trichosurus vulpecula across Australia with mtDNA D-loop sequences (Neaves et al, 2016;Umbrello et al, 2020; Figure 1).…”
Section: Niche Modelingmentioning
confidence: 99%